Anisotropic permeability model considering gas and water adsorption and stress - Xiaoyu ZHANG; Bobo LI; Jianhua LI; Lidan JIA; Yunna DING; Haosheng SONG (Meitan kexue jishu)
As an unconventional natural gas resource, the rational exploitation of coalbed methane (CBM) is conducive to the reduction of gas outflow, the promotion of clean energy and low-carbon development, and the elimination of major gas accident hazards. However, the anisotropy of the internal structure of coal rock and its gas-water coexistence environment make the gas seepage behaviour very complicated. In order to investigate the gas seepage law during the extraction process, this paper constructs an anisotropic permeability model based on the anisotropic structural characteristics of coal rock and the cubic law, which takes into account the effects of water content, gas pressure and stress. The gas-absorption expansion parameter Cs and water-absorption expansion parameter Cθ are proposed to quantify the matrix adsorption gas-induced expansion deformation and matrix adsorption water-induced expansion deformation. Comparing the published test data with the calculated values of the permeability model in this paper, the model calculation results are consistent with the change rule of the test data, and the proposed model better reflects the gas seepage characteristics under the synergistic effect of gas and water adsorption and stress. The results show that: under the action of true triaxial stress, the permeability in different directions differs, and the gas seepage shows strong anisotropy; under constant gas pressure and external stress, the permeability shows a decreasing trend with the increase of water content; the change of permeability with the water content shows an opposite trend to the change of Cθ with the water content, and the same trend to the change of Cs with the gas pressure; in the sensitivity analyses, the 10% positive and negative perturbations were applied to the gas-absorption expansion parameter Cs, the water-absorption expansion parameter Cθ and the porosity φ, respectively, and it was found that Cθ had the greatest influence on the evolution of coal rock permeability, and the porosity φ had the smallest influence on the evolution of coal rock permeability. The results of the study can provide a theoretical basis for accurately assessing the permeability of coal rock, and also provide theoretical guidance for improving the gas extraction rate.